Survivance in Indigenous Schools: Wayuu Students’ Resistance to Coloniality in La Guajira (Colombia) - Gutierrez, Claudia Patricia (Íkala, Revista de Lenguaje y Cultura, 2025)
Colonial language policies and teaching practices continue to impact Indigenous people’s languages and epistemologies both in and out of their territories, even when Indigenous students attend schools intended to sustain their lifeways. In this critical case study, I examine the multifaceted dimensions of coloniality that Wayuu students from La Guajira, Colombia, continue to endure in their education. However, because Indigenous peoples are not passive in their navigation of coloniality, I also describe their unwavering commitment to accessing education in their own territory and the multiple forms of resistance Wayuu students engage in to sustain their linguistic and cultural identities. This article, therefore, is not about survival, but survivance. It is about Wayuu ninth-grade students’ ongoing stories of survival and resistance against the coloniality of power, being, and knowledge, which pushes for linguistic assimilation into Spanish language and dominates their schooling experience. This coloniality, which is buttressed by colonial education policies, standardized testing, and discourses of globalization and social mobility disregards their Native ways of knowing and doing. I conclude this article by arguing for the need of epistemic disobedience to challenge and transform the colonial systems enforced by educational institutions and policymakers, who continue to advance coloniality on Native lands.